2023
DOI: 10.3390/ijms241813720
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Transcriptomic and Biochemical Signatures of Bacillus subtilis Strains: Impacts on Plant Growth and Abiotic Stress Tolerance

Peter E. Chang,
Yun-Hsiang Wu,
Ciao-Yun Tai
et al.

Abstract: Rhizobacteria from various ecological niches display variations in physiological characteristics. This study investigates the transcriptome profiling of two Bacillus subtilis strains, BsCP1 and BsPG1, each isolated from distinct environments. Gene expression linked to the synthesis of seven types of antibiotic compounds was detected in both BsCP1 and BsPG1 cultures. Among these, the genes associated with plipastatin synthesis were predominantly expressed in both bacterial strains. However, genes responsible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 119 publications
(139 reference statements)
0
4
0
Order By: Relevance
“…4). Previously, inoculation with Bacillus species significantly upregulated chlorophyll-binding proteins in A. thaliana (Chang et al 2023) and led to improvement of chlorophyll content and photosynthesis rate in other plants (Jang et al 2018;. Auxin and SA pathways were significantly enriched in our study, which can directly correlate with the root development of A. thaliana under drought stress.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…4). Previously, inoculation with Bacillus species significantly upregulated chlorophyll-binding proteins in A. thaliana (Chang et al 2023) and led to improvement of chlorophyll content and photosynthesis rate in other plants (Jang et al 2018;. Auxin and SA pathways were significantly enriched in our study, which can directly correlate with the root development of A. thaliana under drought stress.…”
Section: Discussionmentioning
confidence: 49%
“…2), the transcriptome indicated that the bacterium upregulated many plant genes involved in auxin response (Table 3, Table S6). Phytohormone production by PGPRs is a well-studied area (Li et al 2023), and previously, B. subtilis showed auxin and SA pathway enrichment in A. thaliana (Chang et al . 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After three treatments, the fresh weight and floral inflorescence of the seedlings were recorded. Furthermore, both the lignin content and the activity of antioxidant enzymes, including ascorbate peroxidase (APX) and guaiacol peroxidase (POD), were analyzed, following the procedures described by Chang et al [ 141 ].…”
Section: Methodsmentioning
confidence: 99%